Effect of laser process loops on the hole diameter and hole formation of laser micro drilling on tc4 - Ku Ahmad Irfan Fitri, Adzman; Aiman, Mohd Halil; Mahadzir, Ishak@Muhammad; Mohd Fadhlan, Mohd Yusof; Luqman Hakim, Ahmad Shah (Institute of Physics, 2024)
Laser micro drilling stands as a precise manufacturing method that employs a focused laser beam to craft accurate, small holes within a diverse array of materials. Its applications span across vital industries like aerospace, medical, and electronics, playing a pivotal role in creating components like fuel injectors, medical implants, and microelectronics. Within this context, a notable challenge emerges in obtaining a refined surface finish during laser micro drilling. This study delves into the impact of a laser loop, a crucial parameter, on the surface quality of TC4, also known as Ti6Al4V - an aerospace staple. Employing a Conventional Fiber Laser with a peak output of 30 W, the experiment meticulously directs the laser beam onto the TC4 surface via a microscope objective lens. The drilling process unfolds in controlled conditions, mitigating external variables such as temperature and humidity. Assessment of drilled hole surfaces transpires through both light and 3D microscopes. Interestingly, holes subjected to higher laser power and increased laser loop rates demonstrate enhanced surface smoothness. In essence, this inquiry demonstrates the substantial influence of laser loop on TC4's surface finish during laser micro drilling. Elevating the laser loop factor leads to heightened surface refinement and diminished roughness in drilled holes. It was found that the diameter entry of the micro-holes was increased by 61% - 89.35% and the diameter exit of the micro-holes also increased by 55.55% - 62.79%. The outcomes of this investigation offer valuable insights for refining the laser micro drilling process to achieve premium surface quality on TC4 and comparable materials. As such, these findings extend guidance for optimal laser loop settings in the realm of laser micro drilling across various materials, benefiting future manufacturing endeavors.